2023
DOI: 10.1007/s43032-022-01153-0
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Prelabor Rupture of Membranes Linked to Vaginal Bacteriome of Pregnant Females in the Early Second Trimester: a Case-Cohort Design

Abstract: Preterm prelabor rupture of membranes (PPROM) is a major cause of spontaneous preterm birth (sPTB), one of the greatest challenges facing obstetrics with complicated pathogenesis. This case-cohort study investigated the association between vaginal bacteriome of singleton pregnant females in the early second trimester and PPROM. The study included 35,255 and 180 pregnant females with PPROM as cases and term-birth without prelabor rupture of membranes (TWPROM) and term prelabor rupture of membranes (TPROM) pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…A recent study found that the presence of Lactobacillus mulieris, a new species of Lactobacillus discovered in 2020, was associated with a lower risk of PPROM. Typical pathogens such as Megasphaera, Faecalibacterium and Bifidobacterium were also observed in patients with PPROM [64]. The aforementioned studies in various countries based on different populations have made similar findings.…”
Section: Vaginal Microbiota and Premature Rupture Of Membranesmentioning
confidence: 52%
“…A recent study found that the presence of Lactobacillus mulieris, a new species of Lactobacillus discovered in 2020, was associated with a lower risk of PPROM. Typical pathogens such as Megasphaera, Faecalibacterium and Bifidobacterium were also observed in patients with PPROM [64]. The aforementioned studies in various countries based on different populations have made similar findings.…”
Section: Vaginal Microbiota and Premature Rupture Of Membranesmentioning
confidence: 52%
“…It has not been clarified whether the markers of inflammation in the cervical fluid are related to those in the intrauterine environment or merely represent a feature of the overall hyperresponsiveness to specific infectious agents. However, it is undeniable that these factors that influence the variation of the microbial-host interaction play an important role in individual sensitivity and adverse pregnancy outcomes ( 25 - 30 ).…”
Section: Discussionmentioning
confidence: 99%